Superior Information, Income Shocks, and the Permanent Income Hypothesis - Pistaferri, Luigi (The Review of Economics and Statistics, 2001)
According to the permanent income hypothesis with quadratic preferences, households save for a rainy day the transitory component of income innovations and consume entirely the permanent one. The model also rules out precautionary saving. Typically, income shock components are not separately observable, and information on the conditional variance of income is hard to come by. We show how to combine income realizations with subjective expectations to identify separately the transitory and the permanent shock to income and to obtain a measure of idiosyncratic uncertainty, thus providing a powerful test of the theory in short panels. The empirical analysis is performed on a sample of Italian households drawn from the 1989–1991 Survey of Household Income and Wealth.